Efektivitas Hexetidine dan Chlorhexidine sebagai Oral Hygiene terhadap Pencegahan Ventilator-Associated Pneumonia pada Pasien ICU - Nasrullah Nasrullah; Syaiful Syaiful; Ismail Ismail (Celebes Health Journal, 2026)
Background: Ventilator Associated Pneumonia (VAP) is a common nosocomial infection in patients on mechanical ventilators in the ICU and contributes to increased morbidity and mortality. Preventive measures through oral hygiene using antiseptics are an important strategy in reducing the risk of VAP. Objective: This study aims to compare the effectiveness of hexetidine 0.1 % and chlorhexidine 0.2 % in preventing VAP. Methods: The study used a quasi-experimental design with two groups of 30 ICU patients on mechanical ventilators. Group A (n=15) received hexetidine 0.1 % and group B (n=15) received chlorhexidine 0.2 %, each twice daily. The incidence of VAP was measured using the Clinical Pulmonary Infection Score (CPIS). Results: The results showed a lower CPIS score and VAP incidence in the chlorhexidine group (26.7 %) compared to the hexetidine group (66.7 %), with a Relative Risk of 0.40 (p<0.05). Multivariate analysis showed chlorhexidine as an independent protective factor. . Conclusions: It was concluded that 0.2 % chlorhexidine was more effective in preventing VAP in ICU patients.